Analysis Of The Influence Of Digital Technology On BPJS Employement Service During The Corona Virus Disease (COVID-19) Pandemi - Relista, Gia (Indonesian Development of Economics and Administration Journal, 2024)
This study aims to find out about what is meant by public services, especially services at BPJS Employment, how is the BPJS Employment service system during the Covid-19 pandemic, what is the influence of digital technology on BPJS Employment services in Indonesia. The method used in this research is descriptive research where the data is described qualitatively. The research data is limited to public information data provided by Employment BPJS through the website, in particular the 2019 integrated annual report on aggressive growth for the continuous protection of Employment BPJS as well as news and event information. After the enactment of Large-Scale Social Restrictions (PSBB) caused by the Covid-19 pandemic, BPJS Ketenagakerjaan has innovated to change the services it has, one of which is by utilizing digital technology, namely providing services online. This is part of BPJS Ketenagakerjaan’s efforts to continue to provide optimal public services during this pandemic